Physical violence experienced and witnessed by siblings of persons with schizophrenia in Japan. Issue 1 (2nd January 2019) - Kageyama, Masako; Solomon, Phyllis
Abstract: Violence committed by patients with mental illness is mostly perpetuated against family members, not strangers. The present study aimed to clarify the rate of violence that is experienced and/or witnessed by siblings of patients with schizophrenia and factors related to sibling's experiencing and/or witnessing violence committed by patients. A self-administered survey was completed by family members of patients with schizophrenia, including siblings. The final sample consisted of 113 siblings. Of the 113 siblings, 52 (46.0%) had experienced and 56 (49.6%) had witnessed physical violence at some point. A logistic regression revealed that siblings tended to experience physical violence by patients with younger age of onset of the disorder. Witnessing physical violence was significantly related to being a female sibling, a male patient, younger age of patient, and younger age of onset of schizophrenia. Crisis intervention and respite services for female siblings in particular need to be developed in Japan.